Nutritional intervention of MAFLD grounded by multiomics profiling - Low, Zun Siong (Nanyang Technological University, 2023)
Metabolic-associated fatty liver disease, MAFLD, is the most common cause of liver injury, affecting approximately a quarter of the global population. Despite its prevalence and potential harm to the population and economy, efforts to understand and treat the disease have been fruitless. Its long and silent progression makes it extremely difficult to recruit patients to better understand disease etiology. As such, research efforts must be aided by preclinical models to provide better insight. Using a combination of thermoneutral housing and a purified high-fat diet, we characterized a model that displays the full spectrum of MAFLD with rapid progression to NASH. These mice showed various metabolic aberrations, such as obesity, metabolic inflexibility, impaired glucose homeostasis and insulin tolerance. Transcriptomic analysis of the model also revealed important hallmarks of progression, which were further supported by histological evidence. Other biochemical analyses, such as cytokine analysis and lipidomics, also concurred with these results. Importantly, the transcriptomic signature of our LIDPAD model aligns greatly with that of human NASH patients. This allowed us to improve MAFLD staging resolution in human NASH patients. Metagenomic evidence also pointed us towards early gut dysbiosis and liver ROS elevation, suggesting underlying early events to be the driver of NASH. We also identified a potential pathway whereby diet could affect gut leakage and disturb gut microbiota. cAngptl4, a secreted protein associated with tumorigenesis and inflammation, was upregulated in the intestinal epithelium. Further in vivo experiments suggest that this action is influenced by the fatty acid-induced PPARα pathway.